Reading in Colors: Highlighting for Active Reading in Religious Studies - Engler, Steven (Teaching theology and religion, 2001)
This note from the classroom suggests that multicolor highlighting is a useful study technique for religious studies students. The note first reviews the literature regarding the effectiveness of traditional highlighting, then discusses advantages of the modified technique. Monochrome highlighting works only if readers select text through a discriminating reading process. Reading in colors fosters this sort of active reading. It prompts readers to ask how and why a given term, phrase or passage is important. This technique can help students grasp the basic categories and concepts of the discipline and it can embody course requirements or learning outcomes. The note concludes with practical suggestions for using the technique in the classroom.